RELIGIOUS MODERATION IN COUNTERING RADICALISM (CASE STUDY IN SUMBERSEWU VILLAGE, MUNCAR DISTRICT, BANYUWANGI REGENCY) - Ahmad Hariono; Isnaini Isnaini (FORPIM PTKIS ZONA TAPAL KUDA, 2023)
Indonesia is a diverse country consisting of ethnicities, races and religions, which are different so tolerance is needed in understanding all existing differences, In the context of preventing radicalism in Indonesia, religious moderation as the main indicator to maintain a peaceful, tolerant and respectful Indonesia. By strengthening religious moderation in various lines of society and institutions, it is hoped that religious people can position themselves appropriately in a multireligious Indonesian society, so that social harmonization and social life balance occur. Although there are many platforms/conceptions in countering radicalism, the conception of religious moderation is considered very fitting with the conditions of the State of Indonesia based on Bhinneka Tunggal Ika. The purpose of this study is to focus on the attitude of religious life of Sumbersewu Village residents, the participation of Village Government and community organizations in implementing the conception of religious moderation while still paying attention to existing local wisdom. Furthermore, the method used in this study is to use qualitative methods. The results of this study can be concluded that religious moderation is an important element in counteracting radicalism in the name of religion. With this article, it is hoped that it can add scientific treasures in the application of religious moderation in the midst of public life as a basis for counteracting radicalism in Indonesia.